EZH2 Inhibition Compromises α4-1BB-Mediated Antitumor Efficacy by Reducing the Survival and Effector Programming of CD8+ T Cells - Stairiker, Christopher J.; Pfister, Sophia Xiao; Hendrickson, Eleanore; Yang, Wenjing; Xie, Tao; Lee, Catherine; Zhang, Haikuo; Dillon, Christopher; Thomas, Graham D.; Salek-Ardakani, Shahram (Frontiers in Immunology, 2021)
Enhancer of Zeste Homolog 2 (EZH2) inhibitors (EZH2i) are approved to treat certain cancer types. Previous studies have suggested the potential to combine EZH2i with immune checkpoint blockade targeting coinhibitory receptors like PD-(L)1 and CTLA-4, but whether it can also enhance the activity of agents targeting costimulatory receptors is not known. Here, we explore the combination between EZH2i and an agonist antibody targeting the T cell costimulatory receptor 4-1BB (α4-1BB). Our data show that EZH2i compromise the efficacy of α4-1BB in both CT26 colon carcinoma and in an in vivo protein immunization model. We link this to reduced effector survival and increased BIM expression in CD8+ T cells upon EZH2i treatment. These data support the requirement of EZH2 function in 4-1BB-mediated CD8+ T cell expansion and effector programming and emphasize the consideration that must be given when combining such antitumoral therapies.